Food Habits of Eriphia Verrucosa (Eriphiidae) and Pachygrapsus marmoratus (Grapsidae) in the Mediterranean Coast of Eastern Libya in Sosa - Hind Abdrabba; Ayiman Faraj (AlQalam Journal of Medical and Applied Sciences, 2024)
The current study aims to determine the type and abundance of food for two species of crabs, Pachygrapsus marmoratus and Eriphia verrucosa, that inhabit the rocky beaches in the south. Mediterranean coast. A total of 40 crabs of each species collected during 2022 were used. We found that P. marmoratus and Eriphia verrucosa are carnivores, meaning they feed on what is available in their environment. Gastric fullness was determined. Food availability in habitats. The abundance of food in the stomach varies according to varieties, but the general trend was molluscas and crustaceans > Cnidarians > Algae > Seaweed > Fish; this is for the Pachygrapsus crab. Marmoratus, but the general trend was molluscas and cnidarians > And fish > Seaweed > And crustaceans > And algae. This is for the crab Eriphia verrucosa. This study provides information on the abundance and type of food by examining the stomach and knowing the percentage of its fullness and the type and abundance of food in the stomach. تم تحليل محتويات معدة عينات السلطعون الرخامي،وجد نسبة امتلاء المعدة أقل من 25% في 5 عينات. وكانت نسبة امتلاء المعدة 25% في 4 عينات. وكانت نسبة امتلاء المعدة 50% في 18 عينة. وكانت نسبة امتلاء المعدة 75% في 10 عينات. وكانت نسبة امتلاء المعدة 100% في 3 عينات. يتكون النظام الغذائي لسلطعون الصخور بشكل أساسي من الرخويات والقشريات واللواسع بنسبة 40 و30 و12% على التوالي. تم استهلاك الطحالب بنسبة 8% والأعشاب البحرية بنسبة 5% والأسماك بنسبة 5 .% تم تحليل محتويات معدة عينات السلطعون الأصفر،ووجد أن نسبة امتلاء المعدة أقلمن 25% في عينتين. بلغت نسبة الامتلاء في المعدة 25% في 4 عينات،وبلغت نسبة الامتلاء في المعدة 50% في 8 عينات،وبلغت نسبة الامتلاء في المعدة 75% في 12 عينة،وبلغت نسبة الامتلاء في المعدة 100% في 14 عينة. يتكون النظام الغذائي للسلطعون الأصفربشكل رئيسي من الرخويات، واللاسعات، والأسماك، بنسبة 30،و20،و20% على التوالي،وتم استهلاك الأعشاب البحرية بنسبة 15%،والقشريات بنسبة 10%،والطحالب بنسبة 5.%